Relationship Between Social Corporate Disparage, Indigent Corporate Philanthropy, Consumer Recognition Leading to Consumer Disenchantment : Assessing the Moderating Role of Gender - Rai, Ashutosh; Chawla, Udit; Chattopadhyay, Subrata (Indian Journal of Marketing, 2024)
Purpose : Effective brand management is critical to the success of any organization. Managing the animosity and hostility of customers is one crucial aspect. In the marketplace, brand hatred is common and has the power to damage a company’s reputation seriously. Consumer trust could be undermined by this kind of animosity, which might stem from perceived shortcomings, ethical dilemmas, or competitive competition. This study aimed to examine the moderating role of gender on consumer recognition, business philanthropy for the impoverished, societal-corporate disrespect, and consumer disillusionment. Design/Methodology/Approach : Structured questionnaires were used to collect the data. Data was gathered by visiting shopping malls in major metropolitan areas across India. AMOS 26.0 was used for analysis purposes. Systematically, this study tested the validity of all the constructs. Findings : Comparatively speaking, women have a positive moderating influence on consumer recognition, consumer disillusionment, corporation discredit in society, and impoverished corporate giving. Customers’ disillusionment is greatly influenced by societal-corporate disparity, poor corporate generosity, and customer recognition. Practical Implications : The study could help businesses by improving their understanding of brand haters and could be used by managers as a tool to identify factors of brand hate and better deal with it. Businesses could use this information to make marketing tactics to combat negative perceptions of brands. Originality / Value : This paper is one of the pioneering efforts to investigate the moderating impact of gender on brand hate constructs, and it proposes a unique model.